Flourishing, relationship and self - Pellegrini, Sara (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In the knowledge society, the question of self-determination is attentive to the interacting and educational dynamics and through the terms of self, relationship and thriving new opportunities with connections can be generated, promoting pro-sociality. Rahe and Jansen (2023) noted how everyone aspires to happiness and personal well-being in relation to self-love, pro-sociality and nature.